Nickel zirconia cerate cermet for catalytic partial oxidation of ethanol in a solid oxide fuel cell system - Wang, Wei; Su, C.; Zheng, T.; Liao, M.; Shao, Zongping (Elsevier Ltd, 2012)
Ni + CexZr1−xO2 (x = 0.0, 0.2, 0.4, 0.6, 0.8 and 1.0) cermets were synthesized and their catalytic performance for partial oxidation of ethanol (POE) reaction was studied. The structure, reducibility properties and carbon deposition behavior of the various catalysts were investigated. Among the various catalysts, Ni + Ce0.8Zr0.2O2 displayed the best catalytic activity in terms of H2 selectivity and also the highest coking resistance. The fuel cell with Ni + Ce0.8Zr0.2O2 catalyst layer delivered a peak power density of 692 mW cm−2 at 700 °C when operating on ethanol–O2 gas mixtures, comparable to that applying hydrogen fuel. The fuel cell also showed an improved operation stability on ethanol–O2 fuel for 150 h at 700 °C. Ni + Ce0.8Zr0.2O2 is promising as an active and coke-tolerant catalyst layer for solid oxide fuel cells operating on ethanol-O2 fuel, which makes it highly attractive by applying biofuel in an SOFC system for efficiency electric power generation.